Mutations and pituitary morphology in a series of 82 patients with PROP1 gene defects - Obermannova, Barbora; Pfaeffle, Roland; Zygmunt-Gorska, Agata; Starzyk, Jerzy; Verkauskiene, Rasa; Smetanina, Natalija; Bezlepkina, Olga; Peterkova, Valentina; Frisch, Herwig; Cinek, Ondrej; Child, Christopher J; Blum, Werner F; et al. (Hormone research in paediatrics, 2011)
BACKGROUND/AIMS: Defects of the PROP1 gene are the most prevalent genetic cause of combined pituitary hormone deficiency. Previous observations in affected patients have shown pituitary size ranging from hypoplasia to overt pituitary mass and evolution of size over the lifespan. METHODS: We evaluated pituitary size and morphology in PROP1-mutation carriers who originated from Central and Eastern Europe. We analyzed 112 pituitary magnetic resonance imaging (MRI) scans from 82 patients (42 males) aged 2.5-72.7 (median 16.6) years from 60 kindreds. RESULTS: Among the 120 independent PROP1 alleles, the most prevalent mutations were delGA301/302 (99 alleles) and delA150 (13 alleles). Median pituitary height at first MRI was 4.7 mm (range 1.0-20.7) and median volume was 127.6 mm(3) (range 7.5-3,087.0). Pituitary size did not differ between sexes and did not correlate with hormonal phenotype, but significantly decreased with increasing age. However, evaluation of individual values suggested a biphasic mode with increasing volume during childhood, peak in adolescence, and subsequent regression in adulthood. CONCLUSION: Although pituitary size was increased in a number of PROP1-deficient patients, none of them suffered permanent damage from pituitary mass; therefore, any proposed surgery should be postponed as long as possible and ultimately may not be necessary due to the self-limiting nature of the pituitary enlargement.
Keywords: senioři; hypofýza; Pituitary Gland; Homeodomain Proteins; Hypopituitarism; mladiství; Cohort Studies; Radiography; hypopituitarismus; Middle Aged; mužské pohlaví; mutace; Adult; mladý dospělý; kohortové studie; dítě; Child; magnetická rezonanční tomografie; Organ Size; Child, Preschool; velikost orgánu; Magnetic Resonance Imaging; Young Adult; ženské pohlaví; radiografie; Mutation; Humans; předškolní dítě; lidé středního věku; dospělí; Female; Aged; Adolescent; homeodoménové proteiny; lidé; Male